Correction: Elastic strain effects on catalysis of a PdCuSi metallic glass thin film. Issue 18 (20th April 2017) - Yang, Yiyi; Adit Maark, Tuhina; Peterson, Andrew; Kumar, Sharvan
Abstract : Correction for 'Elastic strain effects on catalysis of a PdCuSi metallic glass thin film' by Yiyi Yang et al., Phys. Chem. Chem. Phys., 2015, 17, 1746–1754.